Explanation:
The sum of ages of two friends is 13 years.
The product of their ages is 42.
Let the age of 1st friend and 2nd friend is x, y respectively.
1 st condition= The sum of ages of two friends is 13 yrs.
i.e x+y = 13........ (I)
2nd condition= The product of their ages is 42.
i.e X*y = 42........(ii)
From equation (I)
X+y = 13
or, X = 13-y........ (iii)
Putting the equation (iii) in equation (ii).
X*y= 42
(13-y) * y = 42
13y - y^2 = 42
Either; y-6 = 0
y = 6
Or;
y-7=0
y = 7
Keeping the value of y as "7" in equation (ii)
x*y = 42
7x = 42
X = 42/7
Therefore, the value of X is 6.
Therefore, either 1st friend is 6 years and 2nd is 7 years.
Hope it helps...